Improving stimulated Brillouin scattering mitigation in weakly-damped plasmas: from spectral dispersion to spectral distribution. (15th November 2021) - Fusaro, A.; Loiseau, P.; Penninckx, D.; Riazuelo, G.; Collin, R.
Abstract: Optical smoothing techniques are widely used in large high-power laser facilities designed for inertial confinement fusion research, such as the Laser Mégajoule (LMJ) in France. Those techniques are of primordial interest because they reduce laser–plasma instabilities as, for example, the stimulated backward Brillouin scattering (SBS). The latter takes place in the hot plasmas produced inside a hohlraum by the ablation of high- Z or gold material where ion acoustic waves are weakly damped, easing SBS. However, despite the current optical smoothing implementation, like smoothing by spectral dispersion (SSD), SBS is not sufficiently mitigated and may also damage the laser optics by following back the laser path. Moreover, SSD limits the available energy and may produce unwanted amplitude modulations in the laser chain, resulting in an additional damage. Using spectral distribution with two colors (Duluc et al 2019 Phys. Rev. Appl. 12 054055) has proven to limit the latter damage, keeping the same efficiency for limiting SBS. In this study, we go a step forward and generalize this approach by exploring multi-color spectral distribution schemes and the role of dispersion by means of three-dimensional simulations. This study paves the road to new laser concepts that could tackle more efficiently the laser–plasma interaction issues leading to a better laser energy coupling.